FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA UNTUK BERINVESTASI DI PASAR MODAL - Nugraha, Ida Bagus Adipramana; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Investment in the capital market can be used as an alternative to investing for people who want to invest their money and contribute for economic growth in a country. However, the number of investors in Indonesia in quantity is still far from the population in Indonesia. This study aims to analyze the factors that influence the interest in investing in the capital market. This research was located at the Faculty of Economics and Business, Udayana University with students of 2018-2019 who had attended the capital market theory course as a population. The sampling technique used was purposive sampling and the sample obtained was 233 respondents with a data analysis technique, namely multiple linear regression analysis. The results of this study indicate that investment knowledge, motivation, family environment and financial literacy have a positive effect on investment interest in the Capital Market.